PENERAPAN METODE Al-BAGHDADI DALAM TAMAN PENDIIDKAN Al-QUR’AN (TPQ) DI MADRASAH IBTIDIAYAH AL-FATTAH KOTA MALANG - Jamilatul Fajriyah; Azhar Haq; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
The Al-Baghdadi method in the Al-Qur'an education park program is a very easy method to understand, because the material discussed by children is easier and more practical, the target material is delivered very clearly and is not used by others. The purpose of this research is to study the Al-Qur'an education park program in the Islamic City of Al-Fattah Malang City and to study the application of Al-Baghdadi in the Al-Qur'an education school in Ibtidaiyah Islam Al-Fattah Malang City. This study uses qualitative and the type of research is a case study. Data obtained by researchers through interviews, interviews, observation. The results showed that the Al-Qur'an education park program using the Al-Baghdadi method in the Madrasah Ibtidaiyah Al-Fattah Malang City was very good and with the enthusiasm of foundations, teachers, parents or guardians of students and children were very supportive in using this method. As for the implementation of activities in the Al-Qur'an education park program using the Al-Baghdadi method, namely: learning to read the Koran, memorizing short surahs, introducing hijaiyah letters and Arabic numerals.